A long noncoding RNA signature for ulcerative colitis identifies IFNG-AS1 as an enhancer of inflammation - Padua, David (Am J Physiol Gastrointest Liver Physiol, 2016)
High-throughput technologies revealed new categories of genes, including the long noncoding RNAs (lncRNAs), involved in the pathogenesis of human disease; however, the role of lncRNAs in the ulcerative colitis (UC) has not been evaluated. Gene expression profiling was used to develop lncRNA signatures in UC samples. Jurkat T cells were activated by PMA/ionomycin subsequently interferon-γ (IFNG) and tumor necrosis factor (TNF)-α protein levels were assessed by ELISA. Anti-sense molecules were designed to block IFNG-AS1 expression. A unique set of lncRNAs was differentially expressed between UC and control samples. Of these, IFNG-AS1 was among the highest statistically significant lncRNAs (fold change: 5.27, P value: 7.07E−06). Bioinformatic analysis showed that IFNG-AS1 was associated with the IBD susceptibility loci SNP rs7134599 and its genomic location is adjacent to the inflammatory cytokine IFNG. In mouse models of colitis, active colitis samples had increased colonic expression of this lncRNA. Utilizing the Jurkat T cell model, we found IFNG-AS1 to positively regulate IFNG expression. Novel lncRNA signatures differentiate UC patients with active disease, patients in remission, and control subjects. A subset of these lncRNAs was found to be associated with the clinically validated IBD susceptibility loci. IFNG-AS1 was one of these differentially expressed lncRNAs in UC patients and found to regulate the key inflammatory cytokine, IFNG, in CD4 T cells. Taking these findings together, our study revealed novel lncRNA signatures deregulated in UC and identified IFNG-AS1 as a novel regulator of IFNG inflammatory responses, suggesting the potential importance of noncoding RNA mechanisms on regulation of inflammatory bowel disease-related inflammatory responses.